Anger, happiness and life-satisfaction among interpersonal or non-interpersonal trauma survivors in Iceland - Thelma Lind Smáradóttir 1991- (2020)
The purpose of this research study was to examine if type of trauma relates to happiness and life-satisfaction among trauma survivors in Iceland, and whether that relationship is mediated by anger. Based on previous research studies, it was hypothesized that trauma was positively associated with anger and negatively associated with happiness and life-satisfaction, that interpersonal trauma was a predictor for greater level of anger, and that anger would mediate the relationship between trauma and happiness, and between trauma and life-satisfaction. Participants were 747 Icelanders, aged 18 to 80 years old, from a sample from Registers Iceland. A binary logistic regression showed that type of trauma is significantly related to happiness, but not life-satisfaction, and does not predict anger. There was not a significant indirect effect of type of trauma on neither happiness, nor life-satisfaction through anger. Indicating that those who have experienced non-interpersonal trauma report greater happiness, compared to those who have experienced interpersonal trauma, but the relationship is not mediated by anger as was hypothesized, although anger was found to be a predictor for less happiness and life-satisfaction. Based on these results, it can be concluded that further research is needed on the relations between trauma and anger, to further establish if anger is indeed a factor that needs to be considered following trauma. Keywords: trauma, interpersonal trauma, non-interpersonal trauma, anger, happiness, life-satisfaction